An Appraisal of Workshop Facilities and Equipment Utilization for Teaching and Learning of Metal Work in Technical Education of Kano State, Nigeria - Ya’u, Rabo; Nafiu, Ismali; Rabiu, Baba Abdullahi; Nura, Saminu Ayuba (Kashere Journal of Education, 2025)
The study was carried out to assess the utilisation level of workshop facilities and equipment for teaching and learning metalwork in technical education in Kano state, Nigeria. A survey research design was employed for the study. The population of the study was 183 metalwork teachers and metalwork students. The sample of the study comprised 32 metalwork teachers and 77 metalwork students, which makes a total of 109 respondents. Structured questionnaire which contains 29 items was used for data collection. Likart was used: Strongly Agree (SA)=5, Agree (A)=4, Undecided (U)=3, Disagree (D)=2, and Strongly Disagree (SD)=1. The questionnaire was validated by three experts from the department of metalwork, school of vocational and technical education, Kano state polytechnic. For the purpose of instrument, cronbach Alpha reliability method was used, which gave a reliability index of 0.85. It was observed that the facilities and equipment in the workshop were not utilised for effective teaching and learning. Instructional material such as audio videos slides, and films were not utilised for teaching and learning, and teachers lacked adequate skills for improvisation. It was also observed that facilities such as machines and equipment will be changed and properly maintained through available funding. Training institute technical teachers should include courses on improvisation in all the trade areas as a mandatory requirement for graduation in Nigeria.